Shift work and overall and cause-specific mortality in the Danish nurse cohort - Jeanette Therming Jørgensen; Sashia Karlsen; Leslie Stayner; Johnni Hansen; Zorana Jovanovic Andersen (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: Evidence of an effect of shift work on all-cause and cause-specific mortality is inconsistent. This study aims to examine whether shift work is associated with increased all-cause and cause-specific mortality. METHODS: We linked 28 731 female nurses (age ≥44 years), recruited in 1993 or 1999 from the Danish nurse cohort where they reported information on shift work (night, evening, rotating, or day), to the Danish Register of Causes of Death to identify deaths up to 2013. We used Cox regression models with age as the underlying scale to examine the associations between night, evening, and rotating shift work (compared to day shift work) and all-cause and cause-specific mortality in models adjusted for potentially confounding variables. RESULTS: Of 18 015 nurses included in this study, 1616 died during the study time period from the following causes: cardiovascular disease (N=217), cancer (N= 945), diabetes (N=20), Alzheimer's disease or dementia (N=33), and psychiatric diseases (N=67). We found that working night [hazard ratio (HR) 1.26, 95% confidence interval 95% CI) 1.05-1.51] or evening (HR 1.29, 95% CI 1.11-1.49) shifts was associated with a significant increase in all-cause mortality when compared to working day shift. We found a significant association of night shift work with cardiovascular disease (HR 1.71, 95% CI 1.09-2.69) and diabetes (HR 12.0, 95% CI 3.17-45.2, based on 8 cases) and none with overall cancer mortality (HR 1.05, 95% CI 0.81-1.35) or mortality from psychiatric diseases (HR 1.17, 95% CI 0.47-2.92). Finally, we found strong association between evening (HR 4.28, 95% CI 1.62-11.3) and rotating (HR 5.39, 95% CI 2.35-12.3) shift work and mortality from Alzheimer's disease and dementia (based on 8 and 14 deaths among evening and rotating shift workers, respectively). CONCLUSIONS: Women working night and evening shifts have increased all-cause, cardiovascular, diabetes, and Alzheimer's and dementia mortality.